Utilization of Fly Ash in the Fertilizer Industry as an Alternative to Synthetic Coagulants with the Addition of H₂SO₄ - Pratama, Bagas Chrisma; Rosariawari, Firra (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
This study aimed to utilize fly ash, a solid waste generated from coal combustion in the fertilizer industry, as an alternative coagulant for wastewater treatment. Fly ash was activated using H₂SO₄ at varying concentrations (2%, 4%, 6%, and 8%) and coagulant dosages (2 mL, 4 mL, and 6 mL). The effectiveness of fly ash as a coagulant in degrading suspended particles and Chemical Oxygen Demand (COD), as well as in reducing wastewater pH, was analyzed using the jar test method. The results demonstrated that fly ash coagulant was effective in reducing Total Suspended Solids (TSS) and COD, with the most significant reduction observed at a dosage of 4 mL and an H₂SO₄ concentration of 8%. Under these conditions, TSS decreased by 82.35% (from 0.79019 kg/ton to 0.13945 kg/ton), while COD decreased by 72.72% (from 0.02045 kg/ton to 0.00558 kg/ton). Correlation analysis indicated a strong relationship between H₂SO₄ concentration, coagulant dosage, and the reduction of TSS and COD. Although effective in reducing TSS and COD, the fly ash coagulant caused a decrease in wastewater pH due to its acidic nature. Further research is required to improve wastewater pH after the addition of fly ash coagulant.